MEMAHAMI PERAN ORGANISASI INTERNASIONAL DALAM HAL INTERVENSI KEMANUSIAAN - Hartana; Nyoman Hapsari Pradnya Dewi (Universitas Pendidikan Ganesha, 2020)
Lack of understanding of how international organizations intervene in humanitarian crises is the driving force behind this study. International organizations serve as a platform for international cooperation and have legal status, authorities, and functions in the sense that they are considered to have a legal personality under international law. This legal personality entails a range of rights and responsibilities, including the capacity to enter into international agreements, the right to privileges, and immunity from locus rights. limited standing before the International Court of Justice, the capacity to file complaints, and responsibility on the part of international organizations for actions that are deemed illegal. The debate over accepting humanitarian intervention in a country is becoming more and more clear among international organizations that engage in a variety of activities in the state's interests. This study aims to outline the difficulties faced by international organizations when intervening in humanitarian situations.